2000
DOI: 10.1076/1388-0209(200004)3821-1ft106
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils of Annual Sideritis Species Growing in Turkey

Abstract: Water distilled essential oils of five annual Sideritis species collected from different regions of Turkey were analysed by GC/MS. Results are tabulated and compared with main components of the essential oils of perennial Sideritis species from Turkey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 5 publications
3
28
1
2
Order By: Relevance
“…40 With this study we contribute to the knowledge of the chemical composition of Spanish flora and to extend the classification proposed by Dr Baser. 19,20 We have found qualitative and quantitative differences between our results and those previously published on this species. 21 Only 29 compounds are common to both studies and 44/73 compounds identified have not been previously reported in this species (Table 3).…”
Section: Resultscontrasting
confidence: 72%
See 1 more Smart Citation
“…40 With this study we contribute to the knowledge of the chemical composition of Spanish flora and to extend the classification proposed by Dr Baser. 19,20 We have found qualitative and quantitative differences between our results and those previously published on this species. 21 Only 29 compounds are common to both studies and 44/73 compounds identified have not been previously reported in this species (Table 3).…”
Section: Resultscontrasting
confidence: 72%
“…Nevertheless, one species of this genus, S. perfoliata, has been described to present diterpenes as major constituents. 19 The oil yield of the species belonging to this genus is highly variable, from 0.02% in S. curvidens 19 to 0.83% in S. congesta, 15 although it could be caused by the variability of this genus, which includes different sections and subsections with annual and perennial species. 37,38 Although the yield seems to change according to the plant biotype, previous studies have also confirmed that the intercrossing species also affect it, as in the case of S. tragoriganum (Table 1 12,13 ).…”
Section: Introductionmentioning
confidence: 99%
“…1991). Kirimer et al. (2000) studied the composition of oils of Salvia phlomoides , Sideritis vulcanica , Sideritis vuralii and Sideritis caesarea .…”
Section: Introductionmentioning
confidence: 99%
“…Prinos etarskog ulja S. montana iznosio je 0,03% (w/w), što odgavara podacima u literaturi za biljnu vrstu S. montana podvrsta montana iz Turske [12]. Na osnovu GC i GC-MS analize etarskog ulja identifikovano je 8 komponenata, koje predstavljaju 100% ukupno detektovanih komponenata (tabela 1).…”
Section: Rezultati I Diskusijaunclassified